Functionalization of SPION nanoparticle with malic acid for the development of superfinish optical surface. (June 2023) - Amir, Md; Sharma, Rohit; Mishra, Vinod; Pant, Kamal K.; Agarwal, Amit K.; Kim, Daewook; Wazed Ali, S.; Khan, Gufran Sayeed
Highlights: A functionalized magnetic nanocomposites-based nanoabrasive has been prepared via a simple and modified hydrothermal route. The polishing performance of the nanoabrasive is investigated at different pH of the slurry and at different polishing time. BK-7 and Fused silica glasses have been explored for the polishing using the developed nanoabrasive-based slurry. The reduced surface roughness (Ra) are noted as 2 Å and 1 Å for BK-7 and Fused silica glasses, respectively. The superparamagnetic nature of the nanocomposites made the prepared nanoabrasives recyclable and reusable for polishing. Abstract: Optical instruments such as X-ray optics, high-power laser systems, synchrotron beamlines, lithography, and laser-based sensors, require a superfine optical surface to meet their tight optical performance tolerances. This study describes the development of a nanocomposite-based nanoabrasive that can provide a superfinish optical surface via optical polishing. The Malic acid as an organic surface modifier is functionalized with the superparamagnetic iron oxide nanoparticles (SPION). Strong chemical attachment between SPION nanoparticles and the Malic acid is verified through fourier transform infrared spectroscopy. A significant enhancement in the surface area and zeta potential value of SPION nanoparticles is observed when it is functionalized with the Malic Acid. The particle size distribution of the functionalized nanoabrasive is also narrowed down to 8–26 nm. The polishing performance of the functionalized SPION nanoabrasive has been investigated on the BK7 and Fused Silica glasses for precision optical polishing. The polishing results showed superfine surface finishing of the BK7 glass and the Fused silica glass down to the Ra value of 0.23 nm and 0.1 nm, respectively.